2022
DOI: 10.1177/10353046221075103
|View full text |Cite
|
Sign up to set email alerts
|

Telework potential in the Philippines

Abstract: Using work from home (WFH) scores obtained by matching Philippine occupations with U.S. O*NET occupations, this paper estimates that only 12.38% of all workers can WFH and 25.7% of Philippine occupations are teleworkable––mostly from the following occupational groups: professionals, clerical support workers, and technicians and associate professionals. The education, real estate and, professional, scientific and technical sectors account for the largest share of teleworkable jobs. Those workers belonging to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In the Philippines, work-from-home (WFH), or telework arrangements were adapted by businesses if their line of work allows their employees to do so. Gaduena et al (2022) estimated that only 25.7% of occupations in the Philippines are teleworkable. Although there was a swift adoption of such measure to those that have the capability to do so, some jobs cannot be performed remotely (Gaduena et al 2022).…”
Section: Overview Of Pandemic Impact Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Philippines, work-from-home (WFH), or telework arrangements were adapted by businesses if their line of work allows their employees to do so. Gaduena et al (2022) estimated that only 25.7% of occupations in the Philippines are teleworkable. Although there was a swift adoption of such measure to those that have the capability to do so, some jobs cannot be performed remotely (Gaduena et al 2022).…”
Section: Overview Of Pandemic Impact Modelingmentioning
confidence: 99%
“…Gaduena et al (2022) estimated that only 25.7% of occupations in the Philippines are teleworkable. Although there was a swift adoption of such measure to those that have the capability to do so, some jobs cannot be performed remotely (Gaduena et al 2022). Further, Gaduena et al (2022) identified that most of the occupations that can support teleworkable jobs are typically found in sectors that have a low share of the country's total employment (i.e., sectors that require at least undergraduate degrees).…”
Section: Overview Of Pandemic Impact Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention to the regulation of workers' rights, especially to support the existence of remote working, is not only the concern of the Indonesian state. ASEAN countries also participated in discussions or even made amendments to their labor laws, such as those carried out by Malaysia (Wahab, Razak, & Mahmod, 2022), Singapore (boundlesshq.com, 2020), Thailand (Koty, 2023) and Philippines (Gaduena, Caboverde, & Flaminiano, 2022) (Mores, 2022). The following is a brief description of the remote working provisions in these countries:…”
Section: Resultsmentioning
confidence: 99%
“…Industry 4.0 involves, among other things, managing the workflow of integrated activities between various processes, devices, and users (Bellini et al, 2022). When evaluating the literature, it is noticeable that there are many studies and reports about how Industry 4.0 changes and will change the local workforce (Bag et al, 2021; Burgess & Connell, 2021; Gaduena et al, 2022; Paz et al, 2022) and how the above-mentioned practices need to evolve (e.g., Flores et al, 2020). The results show that robots and other assistant systems will not replace human workforce.…”
Section: Literature Reviewmentioning
confidence: 99%